Smart world : - Ogle, Richard (Harvard Business School Press, 2007)
Since ancient times, people have believed that breakthrough ideas come from the brains of geniuses with awesome rational powers. In recent years, however, the paradigm has begun to shift toward the notion that the source of creativity lies "out there," in the network of connections between people and ideas. In this provocative book, Richard Ogle crystallizes the nature of this shift, and boldly outlines "a new science of ideas." The key resides in what he calls "idea-spaces," a set of nodes in a network of people (and their ideas) that cohere and take on a distinctive set of characteristics leading to the generation of breakthrough ideas. These spaces are governed by nine laws - illuminated in individual chapters with fascinating stories of dramatic breakthroughs in science, business, and art. "Smart World" will change forever the way we think about creativity and innovation.